(untitled) (Mustansiria Dental Journal, 2018)
Improving the oral health status through out a group directed periodontal health educational programs was and still as one of the most applied strategies in field of dental and periodontal disease prevention. Eighty systemically fit undergraduate dental students were randomly chosen and allocated into two groups (control and experimental). A two-lecture educational program was carried out for both groups, but Students in the experimental group were instructed to use their mobile phone reminder to remind them the time of performing oral hygiene practice. Results of this research clearly reflect the proposed positive effect of the educational program on the oral health status of the participant and highly significant improvement was recorded for those who use the mobile reminder